Zaryadye: the extraordinary adventures of the reserved place - Kudryavtsev, Alexander (project baikal, 2021)
The intervention of the new in the historical heritage is always painful and contains a contradiction between consumers and architects. Conflicts in this sphere accompany the urban development just up to confrontation between the population and authorities. An exit is in the procedure of taking decisions by a dialogue of all participants of the process, its transparency. There is an importance of not only the conservation of heritage but also the persuasion of the new proposal about the future.The example of Zaryadye near Kremlin walls traces the transformation of visions about its development from the modernism of the giant hotel "Rossiya" up to creation of the public city park. For that final decision the image of "wild urbanism" has played the crucial role in syntethis with the contemporary architecture created by American, Danish and Russian designers and urbanists.
Keywords: innovation; heritage; dialogue; transformation; development; wild urbanism